Discovery of novel antagonists of glycoprotein IIb/IIIa-mediated platelet aggregation through virtual screening. Issue 6 (15th March 2015) - Wang, Yawen; Zhao, Yang; Sun, Rui; Kong, Wanjun; Wang, Bing; Yang, Guangde; Li, Yiping
Graphical abstract: Abstract: The glycoprotein IIb/IIIa receptor is the final common pathway of platelet aggregation, regardless of the agonist, and thus represents an ideal therapeutic target for blocking thrombus formation. RUC-2 is a novel glycoprotein IIb/IIIa inhibitor of adenosine-5′-diphosphate (ADP)-induced platelet aggregation, importantly which exhibits a unique mode of binding with respect to classical Arg-Gly-Asp (RGD)-based glycoprotein IIb/IIIa antagonists. To identify new chemotypes that inhibit glycoprotein IIb/IIIa-mediated platelet aggregation like RUC-2, we performed a combination of structure-based pharmacophore screening and structure-based virtual screening approach to screen over 7.3 million small molecules based on the RUC-2–glycoprotein IIb/IIIa crystal structure. Three of the eleven hit compounds identified by virtual screening showed promising activity with IC50 values between 16.9 and 90.6 μmol L −1 in a human platelet aggregation assay induced by ADP and thrombin. The binding conformations of these three were analyzed to provide a rationalization of their activity profile. These compounds may serve as potential novel scaffolds for further development of glycoprotein IIb/IIIa antagonists.